Perancangan dan Penerapan Alat Cuci Tangan Sistem Injak untuk Pola Hidup Baru di Perpustakaan Pesisir Teratai 414 Tambak Mulya Semarang Utara - Adi Kurniawan Yusim; Sunarso Sugeng; Mohd Ridwan; Sarwoko -; Aulia Windyandari; Seno Darmanto; Aristo Bagus Jatmiko; Luthfi Afrizal; Ihsan Maulana Muhammad (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
The Covid-19 pandemic has an impact on all levels of society in Indonesia, including coastal communities in the city of Semarang. This community service program is carried out to create hand washing tools without the need to turn the water tap to support a new lifestyle in the face of the Covid-19 pandemic, which is still a lot in the city of Semarang. Washing hands with soap is part of adapting a new habit after the Covid-19 pandemic hit the world. The method that we use is the manufacture of hand washing tools with a tread system by students of the marine construction engineering engineering technology study program at the Undip vocational school and hand over the equipment to the management of the Perpustakaan Pesisir Teratai 414 in Tambak Mulya, North Semarang District. The method used in this program is the design and manufacture of hand washing equipment with a stomp mechanism. The results of this program show that the community around the library is easier to move there without worrying about not being able to carry out the health protocol, which is to always wash their hands. With the implementation of this program, we can see that the need for the provision of hand washing equipment with a tread system is very high to face this critical period.